Diversidad de microalgas y cianobacterias provenientes de agua del cultivo de arroz del cantón Macará - Eras Guaicha, Jasmania del Cisne (2024)
Rice fields are rich ecosystems that host various species, among them are microalgae and cyanobacteria, which contribute significantly to the fertilization of the crop, because they have the capacity to fix atmospheric nitrogen and carbon to the soil. The objective of this research work was to record the diversity of microalgae and cyanobacteria from rice cultivation in the Macará canton. The water samples were collected randomly in the rice field and transported to the Plant Microbiology Laboratory to begin the isolation where three culture media were used: F/2, BG11 and BG110. The samples were grown in both liquid and solid culture media. For seeding in liquid media, test tubes with 10 ml of mother sample were used, which were maintained at 20 °C with a photoperiod of 12 hours. When they were 14 days old, the cultivation was centrifuged and the pellet was sown on solid medium, sowing by crossstriation. 15 strains were initially isolated in solid BG11 medium, where only 3 got purified. In the second isolation in liquid BG11 medium, 23 pure strains were obtained, of which 22 correspond to microalgae and 1 to cyanobacteria. The taxonomic identification was carried out based on morphology using taxonomic keys where the genera were identified: Ecdysichlamys, Chlorella, Closterium, Pseudanabaena and Raphidocelis, and it was determined that the genus with the greatest presence was Chlorella. In the liquid BG110 medium, four strains were identified, one of microalgae (Chlorococcum) and three of cyanobacteria (2 Pseudanabaena and 1 Anabaena).